2022
DOI: 10.1021/acssuschemeng.2c02113
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Lignin-Based Versatile Bioreinforcement for High-Performance Natural Rubber Composites

Abstract: This work designed a lignin-based reinforcing agent for reinforcing natural rubber (NR) via building up an integrated interfacial network. A facile lignin modification approach was developed using a cyclic anhydride with a long alkene chain, (2dodecen-1-yl)succinic anhydride. The grafting of the modifiers preferentially takes place at the aliphatic −OH sites as indicated by 2D heteronuclear single-quantum coherence and 31 P NMR spectra. The amount of grafted modifier was estimated via TGA, being 27.1 and 48.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…To further explore the energy‐dissipation mechanism, we performed cyclic stretching experiments under varying strains. As shown in Figure 5, the integrated area under the stretching curve represents the energy required for the stretching process, which includes the energy stored in the rubber network and the energy dissipated as heat 38 . Energy dissipation can be triggered by molecular interactions, chain entanglement, or dissociation of filler clusters, and is reflected as the integral area of the corresponding hysteresis loop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the energy‐dissipation mechanism, we performed cyclic stretching experiments under varying strains. As shown in Figure 5, the integrated area under the stretching curve represents the energy required for the stretching process, which includes the energy stored in the rubber network and the energy dissipated as heat 38 . Energy dissipation can be triggered by molecular interactions, chain entanglement, or dissociation of filler clusters, and is reflected as the integral area of the corresponding hysteresis loop.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5, the integrated area under the stretching curve represents the energy required for the stretching process, which includes the energy stored in the rubber network and the energy dissipated as heat. 38 Energy dissipation can be triggered by molecular interactions, chain entanglement, or dissociation of filler clusters, and is reflected as the integral area of the corresponding hysteresis loop. The NRL/silica-PDA-0.18 sample showed a larger hysteresis loop (Figure 5c), demonstrating that the addition of silica-PDA improves the energy dissipation of the latex during the stretching process and realizes a reinforcement effect.…”
Section: Fracture Process and Energy Dissipation Of Nrl/silica-pdamentioning
confidence: 99%
“…In recent years, the application of biobased renewable materials as a potential reinforcing filler has gained interest for the development of sustainable rubber compounds. In this endeavor, lignin recovered from side-streams of, e.g., paper production is being explored extensively due to its abundancy, high carbon content, nonedible nature, and renewability, combined with economic and sustainability benefits. Although numerous publications highlight the potential of different technical lignins like Kraft, lignosulfonate, organosolv lignin, etc., as fillers, the effective utilization of them in high-end rubber applications, e.g., tires, still poses challenges. This is mainly due to its low thermal stability, structural heterogeneity, varied interunit linkages, functionalities, and the diverse specific properties obtained due to differences in the biomass feedstock and the employed biorefinery processes. The sustainable and feasible exploitation of lignin as a filler demands a consistent product with predictable reinforcing properties.…”
Section: Introductionmentioning
confidence: 99%
“…This technique produces thermally stable solid carbonaceous lignin materials with adjustable particle morphology and properties. It also yields different lignins with varying particle size distributions and surface functionalities depending on the process conditions. ,, The presence of still available polar functional groups offers a hydrophilic nature to the HTT lignin and at the same time makes it versatile for surface modification. This is highly beneficial as it can improve the compatibility when incorporated in nonpolar elastomers, as reported in prior arts. Especially, surface modifiers, like organosilane coupling agents (R’Si­(OR) 3 ), are widely used in the rubber industry to overcome the polarity differences between hydrophilic silica fillers and hydrophobic rubbers. These molecules function by anchoring the silica filler and rubber with its two different reactive moieties: (i) the alkoxy group that can attach to the filler surface bearing silanol groups , and (ii) the organo functionality, such as sulfide, mercapto, etc., that can interact with rubber. The advantages of having such a filler–polymer coupling is well known from the silica/silane system. , …”
Section: Introductionmentioning
confidence: 99%
“…or polymer chains (such as the incorporation of polar moieties 32,33 ) should be carried out. Zhu and his co-workers 34 developed a modification approach using a cyclic anhydride with a long alkene chain as a modifier to improve the hydrophobicity of lignin, and reported that the modified lignin/nature rubber composites showed comparable mechanical performance to the CB-filled composites. Liu et al 32,35 reported that the 3-amino-1,2,4-triazole moieties incorporated into the maleic anhydride-modified polyolefin elastomer (POE) could markedly enhance the interfacial interactions between lignin and the nonpolar POE matrix due to the formation of hydrogen bonds and coordination bonds.…”
Section: Introductionmentioning
confidence: 99%